Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/catal10010087
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Selective Photo-Epoxidation of Propylene: A Review

Abstract: The epoxidation of propylene to produce propylene oxide (PO) has a vital role in the industrial production of several commercial compounds and the synthesis of numerous intermediates, fine chemicals, and pharmaceuticals. However, the current PO production processes pose significant problems regarding the environment and economy. The direct photo-epoxidation of propylene using molecular oxygen (an ideal oxidant with active oxygen of 100 wt %) under light irradiation is a promising technology to produce PO. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Excessive body fat increases the risk of other non-communicable diseases (NCD), such as cardiovascular disease (CVD), chronic respiratory disease, metabolic disorders, and certain types of malignant neoplasms [1,2]. Disturbances in adipose tissue function may induce alterations in adipose tissue metabolism (i.e., lipid metabolism/lipolysis) and the storage capacity of dietary lipid in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive body fat increases the risk of other non-communicable diseases (NCD), such as cardiovascular disease (CVD), chronic respiratory disease, metabolic disorders, and certain types of malignant neoplasms [1,2]. Disturbances in adipose tissue function may induce alterations in adipose tissue metabolism (i.e., lipid metabolism/lipolysis) and the storage capacity of dietary lipid in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) defines obesity as excessive body fat accumulation, which is associated with several risks to health [1]. The body mass index (BMI), is used as a surrogate marker for body fat and for classifying obesity, is positively associated with risk factors for cardiovascular and metabolic diseases when BMI is above 18.5 kg/m 2 [4].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, direct epoxidation of propylene by molecular oxygen (DEP) remains a desirable and environment-friendly process for its high atom utilization efficiency . Therefore, considerable effort has been put into the study of the DEP process by researchers .…”
Section: Introductionmentioning
confidence: 99%
“…However, these routes produce a significant amount of coproducts (styrene, ter-butyl alcohol, and dimethyl benzyl alcohol), which heavily depend on market demand. Other processes, such as direction oxidation (catalytic epoxidation and photocatalytic epoxidation), electrochemical, and biochemical processes, also receive considerable attention [1,2,[6][7][8][9][10][11][12][13]. It is noted that an excellent turnover frequency (TOF, 12 s −1 ) could be observed via the biological process [6].…”
mentioning
confidence: 99%
“…Hayashi et al firstly reported that using a mixture of O 2 and H 2 with Au nanoparticles (2-5 nm) dispersed in titanium dioxide (TiO 2 ) could effectively epoxidize propylene to yield PO with favorable results (PO selectivity > 90%, propylene conversion = 1%-2%) [14]. The proposed reaction pathway for the epoxidation of propylene has two steps: (1) hydrogen peroxide is firstly produced on the Au surfaces, and then (2) hydrogen peroxide is transported close to (−OOH) on the tetrahedral-coordinated Ti 4+ centers to react with propylene ( Figure 2) [15][16][17]. Since the proposal of the aforementioned pathway, extensive research has been carried out with regard to designing novel supported Au catalysts (e.g., Au/Ti-contained catalysts) for driven epoxidation.…”
mentioning
confidence: 99%